COVID-19 and liver disease. Issue 11 (14th June 2022) - Dufour, Jean-François; Marjot, Thomas; Becchetti, Chiara; Tilg, Herbert
Abstract : Knowledge on SARS-CoV-2 infection and its resultant COVID-19 in liver diseases has rapidly increased during the pandemic. Hereby, we review COVID-19 liver manifestations and pathophysiological aspects related to SARS-CoV-2 infection in patients without liver disease as well as the impact of COVID-19 in patients with chronic liver disease (CLD), particularly cirrhosis and liver transplantation (LT). SARS-CoV-2 infection has been associated with overt proinflammatory cytokine profile, which probably contributes substantially to the observed early and late liver abnormalities. CLD, particularly decompensated cirrhosis, should be regarded as a risk factor for severe COVID-19 and death. LT was impacted during the pandemic, mainly due to concerns regarding donation and infection in recipients. However, LT did not represent a risk factor per se of worse outcome. Even though scarce, data regarding COVID-19 specific therapy in special populations such as LT recipients seem promising. COVID-19 vaccine-induced immunity seems impaired in CLD and LT recipients, advocating for a revised schedule of vaccine administration in this population.